2022
DOI: 10.1002/anie.202205975
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Role of the Fusion Mode and Electron‐Deficient Core in Fused‐Ring Electron Acceptors for Organic Photovoltaics

Abstract: The A-DA'D-A fused-ring electron acceptors with an angular fusion mode and electron-deficient core has significantly boosted organic photovoltaic efficiency.Here, the intrinsic role of the peculiar structure is revealed by comparing representative A-DA'D-A acceptor Y6 with its A-D-A counterparts having different fusion modes. Owing to the more delocalized HOMO and deeper LUMO level, Y6 exhibits stronger and redshifted absorption relative to the linear and angular fused A-D-A acceptors, respectively. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
5
22
0
Order By: Relevance
“…Coincidentally, while our manuscript was under review, Yi et al theoretically simulated the electronic structures of Y6 and F1 and confirmed that F1 exhibited smaller reorganization energy for the S 0 ↔ S 1 state than Y6 (106 meV for F1; 116 meV for Y6). The smaller reorganization energy is beneficial to the enhanced PLQY, , decreased Stokes shift, and faster exciton diffusion . This theoretical simulation results support the fact that our design is reasonable for improving the PLQY and L D by removing the central electron-deficient group.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Coincidentally, while our manuscript was under review, Yi et al theoretically simulated the electronic structures of Y6 and F1 and confirmed that F1 exhibited smaller reorganization energy for the S 0 ↔ S 1 state than Y6 (106 meV for F1; 116 meV for Y6). The smaller reorganization energy is beneficial to the enhanced PLQY, , decreased Stokes shift, and faster exciton diffusion . This theoretical simulation results support the fact that our design is reasonable for improving the PLQY and L D by removing the central electron-deficient group.…”
Section: Resultssupporting
confidence: 58%
“…The smaller reorganization energy is beneficial to the enhanced PLQY, 43,44 decreased Stokes shift, 39 and faster exciton diffusion. 45 This theoretical simulation results support the fact that our design is reasonable for improving the PLQY and L D by removing the central electron-deficient group. The core synthesis steps of F1 are different from those of traditional Y6 and its derivatives.…”
Section: ■ Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] The molecular design of organic semiconductors is the cornerstone for developing high-performance OSC materials. Since the concept of acceptor-donor-acceptor (A-D-A)-type nonfullerene acceptors (NFAs) was rst proposed by Zhan et al, 11 unparalleled advancements have been witnessed in the power conversion efficiencies (PCEs) of OSCs, thanks to the great efforts devoted to molecular design and synthesis of new NFAs, such as side-chain engineering, 9,[12][13][14][15][16][17][18][19] fused-ring core (D unit) modulation, [20][21][22][23] and terminal group (A unit) modication. 7,8,[24][25][26][27] Usually, most A-D-A-type NFAs have an electron-rich p-conjugated core (D) with sp 3 -hybridized carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk heterojunction (BHJ) organic solar cells (OSCs) have evolved as prospective and affordable alternatives for emerging green energy technologies due to their advantages of abundant raw materials, low cost, light weight, flexibility, large-area fabrication by roll-to-roll manufacture, and readily tunable absorption and energy levels. The power conversion efficiency (PCE) of fullerene-free OSCs has improved significantly over the past decade. , However, the PCE of OSCs still maintains a distance from silicon solar cells and perovskite solar cells, and it still needs improvement before it can be commercialized. To further improve the PCE of OSCs, more efforts should be devoted to the narrow absorption region of organic materials, morphological defects, recombination traps, and the intermolecular interactions between organic molecules. Numerous studies have addressed these problems, for instance, by developing novel materials, controlling vertical stratification in photovoltaic mix films, engineering interfaces, creating ternary devices, and developing new device architectures. Even though tandem OSCs can significantly increase device performance, commercialization is challenging due to the complexity and difficulty of device manufacture. To preserve the single junction structure’s simplicity while improving the active layer’s light absorption, ternary OSCs comprising three light-absorbing materials (a donor, an acceptor, and a third material) in one active layer are demonstrated as an attractive strategy. OSCs based on ternary blends also exhibit great prospects for improving OSCs’ performance because the third component may be capable of adjusting energy levels, enhancing optical absorption range or via Förster resonance energy transfer (FRET) effect, facilitating charge transport, and optimizing phase separation of the active layer. Nowadays, a state-of-the-art PCE exceeding 19% has been achieved in ternary OSCs, which embodies the potential meliority of the ternary strategy in improving PCE. , …”
Section: Introductionmentioning
confidence: 99%